The battle of the forms in international contracts - Senlle Caride, Miguel (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
Despite the doctrinal, legislative and jurisprudence efforts, the special nature of the battle of the forms has made it complicated to find a satisfactory solution to the problem. The present work analyses, from a comparative perspective, the current status quo and how the legal uncertainty produced by the lack of homogeneity affects international contracts. The work concludes with a critical approach to the role that lawyers could play to minimize the negative effects caused by the battle of the forms, emphasizing the importance of contract drafting and contract due diligence.
Keywords: Battle of the forms; CISG; International Contracts; General Terms and Conditions; Foreign Trade